Electrolyte and preparation method thereof, zinc-iron flow battery, electric device and energy storage device
By using electrolyte containing ferrocyanite, alkali and metalporphyrin catalysts in zinc-iron flow batteries, the problems of large voltage loss and low energy efficiency are solved, and higher energy and voltage efficiency are achieved.
Patent Information
- Application Number
- CN202510114394.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-24
Smart Images

Figure CN119812508A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electrolyte and a preparation method thereof, a zinc-iron liquid flow battery, an electrical device and an energy storage device. Background Art
[0002] Alkaline zinc-iron flow batteries using alkaline electrolytes are one of the most promising long-term energy storage batteries in the field of flow batteries. They have the advantages of high energy density, long cycle life, low electrolyte cost, safety and environmental protection. However, the current alkaline zinc-iron flow batteries have the problems of large voltage loss and low energy efficiency. Summary of the invention
[0003] Based on this, it is necessary to provide an electrolyte and a preparation method, a zinc-iron liquid flow battery, an electrical device and an energy storage device that can reduce voltage loss and improve energy efficiency.
[0004] In one aspect of the present application, an electrolyte is provided, wherein the components of the electrolyte include ferrocyanide, alkali, a catalyst and water; the catalyst includes a compound of the following structural formula:
[0005]
[0006] Wherein R is 4-carboxyphenyl, 4-sulfonatephenyl, 4-aminophenyl or 4-phosphorous acid; M is iron (III), cobalt (II), manganese (II) or nickel (II).
[0007] The above-mentioned electrolyte is conducive to the transfer of electrons and protons, thereby increasing the electrochemical reaction rate and ion conductivity, thereby improving the battery energy efficiency and reducing voltage loss.
[0008] The above electrolyte uses a metal porphyrin as a catalyst, and the metal porphyrin has a macrocyclic conjugated structure. The complex formed by the macrocyclic conjugated structure and iron, cobalt, manganese or nickel metal ions can not only achieve homogeneous catalysis, but also effectively reduce the electrochemical reaction energy barrier between ferrocyanide ions and ferrocyanide ions, making the conversion between ferrocyanide ions and ferrocyanide ions faster and more efficient. The 4-carboxyphenyl, 4-sulfonylphenyl, 4-aminophenyl and 4-phosphorous acid on the above metal porphyrin are not only hydrophilic but also can reduce the electrode surface energy, improve the wettability of the electrolyte to the electrode, so that the electrolyte can also be evenly distributed at the electrode interface, promoting homogeneous catalysis. The main function of the alkali in the above electrolyte is to provide a medium for ion conduction, maintain the ion balance inside the battery, and ensure the normal operation of the battery; under alkaline conditions, the iron ions in the ferrocyanide undergo redox reactions to realize the charging and discharging process of the battery, and the metal porphyrin is evenly distributed in the electrolyte, eliminating the concentration gradient, so that the redox reaction is carried out in a more uniform environment. The ferrocyanide, alkali, and metal porphyrin interact with each other and synergistically enhance the efficiency, ultimately improving the energy efficiency and voltage efficiency of the battery and reducing the voltage loss of the battery.
[0009] The catalyst in the above electrolyte does not need to be loaded on the positive electrode or the negative electrode, thus avoiding the problem of catalyst failure that is easily caused by the shedding and loss of the loaded catalyst during long-term circulation.
[0010] The zinc-iron liquid flow battery made using the above electrolyte as the positive electrode electrolyte not only has high energy efficiency and low voltage loss, but also has the advantages of high energy density, long cycle life, low electrolyte cost, and safety and environmental protection.
[0011] In some embodiments, the catalyst includes at least one of tetrakis(4-sulfonatophenyl)porphyrin manganese(II), tetrakis(4-phosphite)porphyrin iron(III), tetrakis(4-carboxyphenyl)porphyrin cobalt(II) and tetrakis(4-aminophenyl)porphyrin nickel(II).
[0012] In some embodiments, the molar concentration ratio of the catalyst to the ferrocyanide ion in the ferrocyanide salt is 0.01% to 0.1%.
[0013] In some embodiments, the concentration of ferrocyanide ions in the electrolyte is 0.2 mol / L to 1.60 mol / L.
[0014] In some embodiments, the concentration of the base is 1.0 mol / L to 6.0 mol / L.
[0015] In some embodiments, the ferrocyanide salt includes at least one of sodium ferrocyanide and potassium ferrocyanide.
[0016] In some embodiments, the base includes at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide.
[0017] In some embodiments, the electrolyte satisfies at least one of the following conditions:
[0018] (1) The components of the electrolyte include sodium ferrocyanide, potassium hydroxide, tetrakis(4-sulfonatophenyl)porphyrin manganese(II) and water;
[0019] (2) The components of the electrolyte include potassium ferrocyanide, sodium hydroxide, tetrakis(4-phosphite)porphyrin iron (III) and water.
[0020] The second aspect of the present application provides a method for preparing an electrolyte, wherein the alkali, the ferrocyanide and the catalyst are mixed in water to prepare the electrolyte.
[0021] In some embodiments, the mixing of the base, the ferrocyanide and the catalyst in water comprises the following steps:
[0022] Firstly, the alkali is dissolved in water to prepare an alkali solution;
[0023] Then, the ferrocyanide and the catalyst are mixed in the alkaline solution to prepare the electrolyte.
[0024] The third aspect of the present application provides a zinc-iron liquid flow battery, comprising a positive electrode electrolyte, wherein the positive electrode electrolyte is the electrolyte described in the first aspect or the electrolyte prepared by the preparation method described in the second aspect.
[0025] The fourth aspect of the present application provides an electrical device comprising the zinc-iron liquid flow battery as described in the third aspect.
[0026] The fifth aspect of the present application provides an energy storage device, comprising the zinc-iron liquid flow battery as described in the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the relationship curve between the number of battery system cycles and coulombic efficiency, voltage efficiency and energy efficiency in comparative example 1.
[0028] Figure 2 The graph is a relationship curve between the number of battery system cycles and the coulombic efficiency, voltage efficiency and energy efficiency in Example 1.
[0029] Figure 3 This is the charge and discharge curve of the battery system in Comparative Example 1.
[0030] Figure 4 This is the charge and discharge curve of the battery system in Example 1. DETAILED DESCRIPTION
[0031] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0033] Zinc-iron flow batteries usually use zinc ions as negative electrode active ions and iron ions as positive electrode active ions. Common positive electrode electrolytes include chloride system, sulfate system and sulfonate system. The chloride ions in the chloride system are highly corrosive and have high corrosion resistance requirements for the battery's electrode materials and battery components, which may reduce the battery's service life and reliability; compared with the chloride system, the conductivity of the sulfate system is relatively low, which may lead to certain limitations on the battery's charge and discharge performance at high current density; the preparation cost of sulfonate iron salt electrolytes is relatively high, which limits their large-scale application, and some sulfonate system electrolytes may have high viscosity problems at high concentrations, affecting ion transport and battery performance. There are also zinc-iron flow batteries whose positive electrode electrolyte active substances are composed of water, ferrocyanide and strong alkali, but the electrochemical reaction energy barrier is high and the reaction rate is slow during the mutual conversion between ferrocyanide and ferrocyanide, which causes the battery to have large voltage loss and low energy efficiency. Currently, researchers increase the positive electrode reaction rate by loading metal-nitrogen-carbon catalysts on the electrode. The advantage of this method is targeted catalysis, but the disadvantage is that the catalyst loaded on the electrode surface is not strong. As the battery charges and discharges and the fluid is flushed, the catalyst loaded on the electrode surface is easily lost or detached and loses its catalytic effect.
[0034] Based on this, in the first aspect of the present application, an embodiment provides an electrolyte, wherein the components of the electrolyte include ferrocyanide, alkali, a catalyst and water; the catalyst includes a compound of the following structural formula:
[0035]
[0036] Wherein R is 4-carboxyphenyl, 4-sulfonatephenyl, 4-aminophenyl or 4-phosphorous acid; M is iron (III), cobalt (II), manganese (II) or nickel (II).
[0037] It is understandable that the four Rs on the same catalyst are the same or different. Optionally, the four Rs on the same catalyst are the same. The catalyst is a compound of the above structural formula, which can be one or more compounds that conform to the above structural formula.
[0038] It is understood that M is a trivalent iron ion, a divalent cobalt ion, a divalent manganese ion or a divalent nickel ion.
[0039] The above-mentioned electrolyte is conducive to the transfer of electrons and protons, thereby increasing the electrochemical reaction rate and ion conductivity, thereby improving the battery energy efficiency and reducing voltage loss.
[0040] The above electrolyte uses a metal porphyrin as a catalyst, and the metal porphyrin has a macrocyclic conjugated structure. The complex formed by the macrocyclic conjugated structure and iron, cobalt, manganese or nickel metal ions can not only achieve homogeneous catalysis, but also effectively reduce the electrochemical reaction energy barrier between ferrocyanide ions and ferrocyanide ions, making the conversion between ferrocyanide ions and ferrocyanide ions faster and more efficient. The 4-carboxyphenyl, 4-sulfonylphenyl, 4-aminophenyl and 4-phosphorous acid on the above metal porphyrin are not only hydrophilic but also can reduce the electrode surface energy, improve the wettability of the electrolyte to the electrode, so that the electrolyte can also be evenly distributed at the electrode interface, promoting homogeneous catalysis. The main function of the alkali in the above electrolyte is to provide a medium for ion conduction, maintain the ion balance inside the battery, and ensure the normal operation of the battery; under alkaline conditions, the iron ions in the ferrocyanide undergo redox reactions to realize the charging and discharging process of the battery, and the metal porphyrin is evenly distributed in the electrolyte, eliminating the concentration gradient, so that the redox reaction is carried out in a more uniform environment. The ferrocyanide, alkali, and metal porphyrin interact with each other and synergistically enhance the efficiency, ultimately improving the energy efficiency and voltage efficiency of the battery and reducing the voltage loss of the battery.
[0041] The catalyst in the above electrolyte does not need to be loaded on the positive electrode or the negative electrode, thus avoiding the problem of catalyst failure that is easily caused by the shedding and loss of the loaded catalyst during long-term circulation.
[0042] The zinc-iron liquid flow battery made using the above electrolyte as the positive electrode electrolyte not only has high energy efficiency and low voltage loss, but also has the advantages of high energy density, long cycle life, low electrolyte cost, and safety and environmental protection.
[0043] In some embodiments, the catalyst includes tetrakis(4-carboxyphenyl)porphyrin iron (III), tetrakis(4-carboxyphenyl)porphyrin cobalt (II), tetrakis(4-carboxyphenyl)porphyrin manganese (II) and tetrakis(4-carboxyphenyl)porphyrin nickel (II), tetrakis(4-sulfonatephenyl)porphyrin iron (III), tetrakis(4-sulfonatephenyl)porphyrin cobalt (II), tetrakis(4-sulfonatephenyl)porphyrin manganese (II), tetrakis(4-sulfonatephenyl)porphyrin nickel (II), tetrakis(4-sulfonatephenyl)porphyrin iron (III), tetrakis(4-sulfonatephenyl)porphyrin cobalt (II), tetrakis(4-sulfonatephenyl)porphyrin manganese (II), tetrakis(4-sulfonatephenyl)porphyrin At least one of tetrakis(4-aminophenyl)porphyrin nickel(II), tetrakis(4-aminophenyl)porphyrin iron(III), tetrakis(4-aminophenyl)porphyrin cobalt(II), tetrakis(4-aminophenyl)porphyrin manganese(II), tetrakis(4-aminophenyl)porphyrin nickel(II), tetrakis(4-phosphite)porphyrin iron(III), tetrakis(4-phosphite)porphyrin cobalt(II), tetrakis(4-phosphite)porphyrin manganese(II) and tetrakis(4-phosphite)porphyrin nickel(II).
[0044] In some embodiments, the catalyst includes at least one of tetrakis(4-sulfonatophenyl)porphyrin manganese (II), tetrakis(4-phosphite)porphyrin iron (III), tetrakis(4-carboxylphenyl)porphyrin cobalt (II) and tetrakis(4-aminophenyl)porphyrin nickel (II). The use of the catalyst further improves the energy efficiency of the battery and further reduces the voltage loss.
[0045] It is understood that the catalyst includes at least one of tetrakis(4-sulfonatophenyl)porphyrin complexed with divalent manganese, tetrakis(4-phosphite)porphyrin complexed with trivalent iron, tetrakis(4-carboxyphenyl)porphyrin complexed with divalent cobalt and tetrakis(4-aminophenyl)porphyrin complexed with divalent nickel.
[0046] In some embodiments, the molar concentration ratio of the catalyst to the ferrocyanide ion in the ferrocyanide salt is 0.01% to 0.1%. In this concentration ratio range, not only the electrochemical reaction energy barrier is lower, the positive electrode reaction rate is higher, but also the overcrowding of the active sites on the positive electrode surface can be avoided, the concentration polarization is reduced, and the homogeneous catalytic effect of the catalyst is further promoted, so that the battery voltage efficiency and energy efficiency are higher and the voltage loss is smaller.
[0047] As an example, the molar concentration ratio of the catalyst to the ferrocyanide ion in the ferrocyanide salt is 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, or can be within the range of any two of the above point values as end values. The molar concentration ratio of the catalyst to the ferrocyanide ion in the ferrocyanide salt is preferably 0.02% to 0.06%. The molar concentration ratio of the catalyst to the ferrocyanide ion in the ferrocyanide salt is more preferably 0.02% to 0.05%.
[0048] In some embodiments, the concentration of ferrocyanide ions in the electrolyte is 0.2 mol / L to 1.60 mol / L. The concentration of ferrocyanide ions within this range is not only conducive to maintaining the ion concentration balance in the positive electrode electrolyte, so that the migration of ions is maintained at an optimal rate, but also can maintain the reaction activity of the positive electrode of the battery, and can avoid concentration polarization, promote homogeneous catalysis of the catalyst, and thus improve the electrical performance of the battery.
[0049] As an example, the concentration of ferrocyanide ions in the electrolyte is 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.5mol / L and 1.60mol / L, and can also be within the range of any two of the above point values as end values. The concentration of ferrocyanide ions in the electrolyte is preferably 0.2mol / L~1.0mol / L. The concentration of ferrocyanide ions in the electrolyte is more preferably 0.4mol / L~1.0mol / L.
[0050] In some embodiments, the concentration of the base is 1.0 mol / L to 6.0 mol / L.
[0051] As an example, the concentration of the base is 1.0 mol / L, 2.0 mol / L, 3.0 mol / L, 4.0 mol / L, 5.0 mol / L and 6.0 mol / L, or it can be within the range formed by any two of the above points as end values. The concentration of the base is preferably 2 mol / L to 4 mol / L.
[0052] In some embodiments, the ferrocyanide salt includes at least one of sodium ferrocyanide and potassium ferrocyanide.
[0053] In some embodiments, the base includes at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide, preferably at least one of sodium hydroxide and potassium hydroxide.
[0054] In some embodiments, the components of the electrolyte include sodium ferrocyanide, potassium hydroxide, tetrakis(4-sulfonatophenyl)porphyrin manganese(II) and water.
[0055] In some embodiments, the components of the electrolyte include potassium ferrocyanide, sodium hydroxide, tetrakis(4-phosphite)porphyrin iron (III) and water.
[0056] The second aspect of the present application provides a method for preparing an electrolyte, wherein the alkali, the ferrocyanide and the catalyst are mixed in water to prepare the electrolyte.
[0057] In some embodiments, the mixing of the base, the ferrocyanide and the catalyst in water comprises the following steps:
[0058] Firstly, the alkali is dissolved in water to prepare an alkali solution;
[0059] Then, the ferrocyanide and the catalyst are mixed in the alkaline solution to prepare the electrolyte.
[0060] The third aspect of the present application provides a zinc-iron liquid flow battery, comprising a positive electrode electrolyte, wherein the positive electrode electrolyte is the electrolyte described in the first aspect or the electrolyte prepared by the preparation method described in the second aspect.
[0061] It can be understood that the zinc-iron flow battery includes not only the above-mentioned positive electrode electrolyte, but also a negative electrode electrolyte, a positive electrode, a negative electrode and a diaphragm, and the diaphragm is arranged between the positive electrode and the negative electrode.
[0062] The active ion at the positive electrode of the alkaline zinc-iron flow battery is ferrocyanide. The redox reaction of ferrocyanide is the main electrochemical reaction occurring at the positive electrode of the alkaline zinc-iron flow battery. The battery is charged and discharged through this process. The active ion at the negative electrode of the alkaline zinc-iron flow battery is zincate.
[0063] In some of the embodiments, the preparation method of the negative electrode electrolyte for the zinc-iron liquid flow battery is: first place the alkali and zinc oxide in a beaker, add 200 mL of pure water, heat in a 60°C water bath and stir, after the zinc oxide is completely dissolved, slowly add 600 mL of pure water, continue stirring until the electrolyte is clear and transparent, stop heating, cool to room temperature, and then adjust the volume for standby use.
[0064] In some embodiments, 300 mL of positive electrolyte and 300 mL of negative electrolyte are placed in a storage tank with an active area of 48 cm 2 The battery system is composed of single batteries.
[0065] In some of the embodiments, the positive electrode of the zinc-iron flow battery uses a carbon material such as carbon felt, graphite felt or carbon cloth.
[0066] In some of the embodiments, the negative electrode of the zinc-iron flow battery uses a carbon material such as carbon felt, graphite felt or carbon cloth.
[0067] In some of the embodiments, the separator of the zinc-iron flow battery is a perfluorosulfonic acid proton exchange membrane.
[0068] The fourth aspect of the present application provides an electrical device comprising the zinc-iron liquid flow battery as described in the third aspect.
[0069] Electrical devices include but are not limited to electric vehicles, electric ships and emergency power supplies.
[0070] The fifth aspect of the present application provides an energy storage device, comprising the zinc-iron liquid flow battery as described in the third aspect.
[0071] Energy storage devices include, but are not limited to, solar power generation systems, wind power generation systems, grid energy storage systems, and uninterruptible power supply systems.
[0072] The following are specific embodiments.
[0073] Example 1
[0074] A zinc-iron flow battery:
[0075] Preparation of negative electrode electrolyte: Weigh 3.0 mol of sodium hydroxide (purity 95%) and 0.2 mol of zinc oxide (purity 99%) in a beaker, add 200 mL of pure water, heat in a 60 °C water bath and stir. After the zinc oxide is completely dissolved, slowly add 600 mL of pure water and continue stirring until the electrolyte is clear and transparent. Stop heating, cool to room temperature and then make up the volume to obtain an electrolyte with a zincate concentration of 0.2 mol / L.
[0076] Preparation of positive electrolyte: weigh 3.0 mol of sodium hydroxide into a beaker, add 400 mL of pure water, heat in a 50 °C water bath and stir. After the sodium hydroxide is completely dissolved, add 300 mL of pure water, then add 0.4 mol of potassium ferrocyanide (purity 99%). After the solution becomes clear, add 0.4×10 tetrakis(4-phosphite)porphyrin iron (III) as the catalyst. -3 mol, i.e. 0.1% of the molar amount of sodium ferrocyanide, after the catalyst is completely dissolved, it is cooled to room temperature and the volume is fixed to obtain an electrolyte with a ferrocyanide concentration of 0.4 mol / L. Among them, tetrakis(4-phosphite)porphyrin iron (III) is commercially available (Xi'an Qiyue Biotechnology Co., Ltd.).
[0077] Take 300 mL of the above positive electrolyte and negative electrolyte respectively in the storage tank and place them in a 48 cm active area tank. 2 The battery system is composed of a single cell, which is assembled with liquid inlet and outlet joints, end plates, hard graphite bipolar plates, electrode frames, sealing gaskets, carbon felt electrodes, perfluorosulfonic acid proton exchange membranes, bolts and nuts; both the positive and negative electrodes use carbon felt electrodes.
[0078] Example 2
[0079] A zinc-iron flow battery:
[0080] Preparation of negative electrode electrolyte: Weigh 3.0 mol of potassium hydroxide (purity 95%) and 0.2 mol of zinc oxide (purity 99%) in a beaker, add 200 mL of pure water, heat in a 60°C water bath and stir. After the zinc oxide is completely dissolved, slowly add 600 mL of pure water and continue stirring until the electrolyte is clear and transparent. Stop heating, cool to room temperature and then make up the volume. The zincate concentration of the electrolyte is 0.2 mol / L.
[0081] Preparation of positive electrolyte: Weigh 3.0 mol of potassium hydroxide into a beaker, add 300 mL of pure water, heat in a 50 °C water bath and stir. After the potassium hydroxide is completely dissolved, add 400 mL of pure water, then add 0.4 mol of sodium ferrocyanide (purity 99%). After the solution becomes clear, add 0.2×10 tetrakis(4-sulfonatophenyl)porphyrin manganese (II) as the catalyst. -3 mol, i.e. 0.05% of the molar amount of sodium ferrocyanide. After the catalyst is completely dissolved, the solution is cooled to room temperature and the volume is fixed to obtain an electrolyte solution with a ferrocyanide concentration of 0.4 mol / L. Among them, tetrakis(4-sulfonatophenyl)porphyrin manganese(II) is a commercially available product.
[0082] Take 300 mL of the above positive electrolyte and negative electrolyte respectively in the storage tank and place them in a 48 cm active area tank. 2 The battery system is composed of single batteries.
[0083] Example 3
[0084] Example 3 is substantially the same as Example 1, except that in the positive electrode electrolyte, an equimolar amount of tetrakis(4-carboxyphenyl)porphyrin cobalt(II) is used to replace tetrakis(4-phosphite)porphyrin iron(III).
[0085] Example 4
[0086] Example 4 is substantially the same as Example 1, except that in the positive electrode electrolyte, an equimolar amount of tetrakis(4-aminophenyl)porphyrin nickel(II) is used to replace tetrakis(4-phosphite)porphyrin iron(III).
[0087] Example 5
[0088] Example 5 is substantially the same as Example 1, except that in the positive electrode electrolyte, the amount of the catalyst tetrakis(4-phosphite)porphyrin iron (III) added is 0.04% of the molar amount of sodium ferrocyanide.
[0089] Example 6
[0090] Example 6 is substantially the same as Example 1, except that in the positive electrode electrolyte, the concentration of ferrocyanide is 1.6 mol / L.
[0091] Comparative Example 1
[0092] A zinc-iron flow battery:
[0093] Preparation of negative electrode electrolyte: Weigh 3.0 mol of potassium hydroxide (purity 95%) and 0.2 mol of zinc oxide (purity 99%) in a beaker, add 200 mL of pure water, heat in a 60 °C water bath and stir. After the zinc oxide is completely dissolved, slowly add 600 mL of pure water and continue stirring until the electrolyte is clear and transparent. Stop heating, cool to room temperature and then make up the volume to obtain an electrolyte with a zincate concentration of 0.2 mol / L.
[0094] Preparation of positive electrode electrolyte: Weigh 3.0 mol of potassium hydroxide into a beaker, add 300 mL of pure water, heat in a 50°C water bath and stir. After the potassium hydroxide is completely dissolved, add 400 mL of pure water, then add 0.4 mol of sodium ferrocyanide (purity 99%). After the solution becomes clear and transparent, cool to room temperature and make up the volume. The electrolyte has a ferrocyanide concentration of 0.4 mol / L.
[0095] Take 300 mL of the above positive electrolyte and negative electrolyte respectively in the storage tank and place them in a 48 cm active area tank. 2 The battery system is composed of single batteries.
[0096] Comparative Example 2
[0097] Comparative Example 2 is substantially the same as Example 1, except that in the positive electrode electrolyte, an equimolar amount of tetraphenylporphyrin is used to replace tetrakis(4-phosphite)porphyrin iron (III), and the structural formula of the tetraphenylporphyrin is as follows:
[0098]
[0099] Wherein, R is phenyl.
[0100] The catalyst in the positive electrode electrolyte in the above embodiments and comparative examples can be commercially available products.
[0101] The battery systems prepared in Examples 1-6 and Comparative Examples 1-2 were tested for energy efficiency and voltage efficiency, and the test results are shown in Table 1 below.
[0102] Among them, the test conditions or test standards for each performance test item are:
[0103] At 80mA / cm 2 The constant current charge and discharge test was carried out with a current density of 30 minutes, the charging time was 30 minutes, the protection voltage was set to 2.2V, and the discharge was set to 0.5V voltage cutoff.
[0104] Energy efficiency is the ratio of discharge energy to charge energy; voltage efficiency is the ratio of average discharge voltage to average charge voltage.
[0105] Table 1
[0106]
[0107] From Table 1 above, we can see that Figure 1 , Comparative Example 1 completed 80 charge and discharge tests, with a voltage efficiency of 80.72% and an energy efficiency of 80.26%; Figure 2 , Example 1 completed 120 charge and discharge tests, with a coulombic efficiency of 98.06%, a voltage efficiency of 90.86%, and an energy efficiency of 89.10%; the voltage efficiency and energy efficiency of Example 1 were respectively increased by about 10.14% and 8.84% compared with Comparative Example 1. Figure 3 , the charge termination voltage of comparative example 1 is 2.03V; combined Figure 4 The charge termination voltage of Example 1 is 1.75V, which is 0.28V lower than that of Comparative Example 1.
[0108] Comparative Example 2 completed 80 charge and discharge tests, with a voltage efficiency of 75.23% and an energy efficiency of 72.3%. There are still problems of large voltage loss and low energy efficiency.
[0109] Example 2 completed 120 charge and discharge tests, with a coulombic efficiency of 97.04%, a voltage efficiency of 88.52%, and an energy efficiency of 85.9%. The voltage efficiency and energy efficiency were approximately 7.8% and 5.64% higher than those of Comparative Example 1, respectively. The charge termination voltage was 1.83 V, which was 0.2 V lower than that of Comparative Example 1.
[0110] The zinc-iron flow batteries prepared in Examples 1 to 6 using a cathode electrolyte comprising ferrocyanide, alkali, metal porphyrin catalyst and water all have high energy efficiency, voltage efficiency and coulombic efficiency.
[0111] In addition, by comparing Example 1 with Example 5, it can be seen that in the above-mentioned positive electrode electrolyte, when the molar concentration ratio of the catalyst to the ferrocyanide ion in the ferrocyanide salt is 0.02% to 0.06%, the energy efficiency and voltage efficiency of the zinc-iron liquid flow battery are higher, and the voltage loss is smaller. By comparing Example 1 with Example 6, it can be seen that in the above-mentioned positive electrode electrolyte, when the concentration of ferrocyanide ions is 0.2 mol / L to 1.0 mol / L, the energy efficiency and voltage efficiency of the zinc-iron liquid flow battery are higher, and the voltage loss is smaller.
[0112] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0113] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An electrolyte, characterized in that: The components of the electrolyte include ferrocyanide, alkali, catalyst and water; the catalyst includes a compound of the following structural formula: Wherein, R is 4-carboxyphenyl, 4-sulfonatephenyl, 4-aminophenyl or 4-phosphorous acid; M is iron (III), cobalt (II), manganese (II) or nickel (II).
2. The electrolyte according to claim 1, characterized in that The catalyst comprises at least one of tetrakis(4-sulfonatophenyl)porphyrin manganese(II), tetrakis(4-phosphite)porphyrin iron(III), tetrakis(4-carboxylphenyl)porphyrin cobalt(II) and tetrakis(4-aminophenyl)porphyrin nickel(II).
3. The electrolyte according to claim 1, characterized in that The molar concentration ratio of the catalyst to the ferrocyanide ion in the ferrocyanide is 0.01% to 0.1%.
4. The electrolyte according to claim 1, characterized in that The concentration of ferrocyanide ions in the electrolyte is 0.2 mol / L to 1.60 mol / L.
5. The electrolyte according to any one of claims 1 to 4, characterized in that The concentration of the alkali is 1.0 mol / L to 6.0 mol / L.
6. The electrolyte according to any one of claims 1 to 4, characterized in that The ferrocyanide salt includes at least one of sodium ferrocyanide and potassium ferrocyanide.
7. The electrolyte according to any one of claims 1 to 4, characterized in that The base includes at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide.
8. The electrolyte according to any one of claims 1 to 4, characterized in that At least one of the following conditions is met: (1) The components of the electrolyte include sodium ferrocyanide, potassium hydroxide, tetrakis(4-sulfonatophenyl)porphyrin manganese(II) and water; (2) The components of the electrolyte include potassium ferrocyanide, sodium hydroxide, tetrakis(4-phosphite)porphyrin iron (III) and water.
9. The method for preparing an electrolyte according to any one of claims 1 to 8, characterized in that: The alkali, the ferrocyanide and the catalyst are mixed in water to prepare the electrolyte.
10. The method for preparing an electrolyte according to claim 9, characterized in that: The step of mixing the alkali, the ferrocyanide and the catalyst in water comprises the following steps: Firstly, the alkali is dissolved in water to prepare an alkali solution; Then, the ferrocyanide and the catalyst are mixed in the alkaline solution to prepare the electrolyte.
11. A zinc-iron liquid flow battery, characterized in that: The invention comprises a positive electrode electrolyte, wherein the positive electrode electrolyte is the electrolyte as claimed in any one of claims 1 to 8 or the electrolyte prepared by the preparation method as claimed in any one of claims 9 to 10.
12. An electrical device, characterized in that: Comprising the zinc-iron flow battery as described in claim 11.
13. An energy storage device, characterized in that: Comprising the zinc-iron flow battery as described in claim 11.
Citation Information
Patent Citations
Positive electrode electrolyte for alkaline zinc-iron flow battery and application
CN111261910A
Porphyrin aqueous zinc ion battery electrolyte additive and application thereof
CN116759670A
Production method of asparagus seedling utilizing root endophyte (DSE) phialocephala fortinii
JP2013042695A
Electrochemical device having regular structure and arranged by using organic active material of high-water solubility and high-energy density
JP2020170697A
Cited By
Flow battery electrolyte and application thereof
CN120527425A